MODEL KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH DAN KEBERHASILANNYA TERHADAP KUALITAS MADRASAH (Studi pada MTsN Watampone) - ABDULLAH K. (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2017)
The purpose of this research are: 1) To know how characteristic of transformational leadership model of head of Madrasah Tsanawiyah State of Watampone. 2) Analyze how the leadership of transformational leadership of Madrasah head toward quality of Madrasah Tsanawiyah Negeri Watampone The results show that: 1) Head of MTsN Watampone is an ideal figure who can be a role model, able to inspire his followers to put their personal interests aside from the interests of madrasah and able to influence and motivate and give personal attention and support to his subordinates. This means that the head of MTsN Watampone proved to be practicing the four dimensions of transformational model leadership namely Idealized influence, Inspirational motivation, Intellectual stimulation, and Individualized consideration. Thus, the Head of MTsN Watampone has proven to have implemented transformational leadership whose success can be seen in the climate and quality of learning and school quality. 2) The successful leadership of MTsN Watampone's transformational leadership on Climate management and learning quality is considerable and good enough, which can be seen through lifestyles embodied based on a set of values or norms, habits supported by adequate facilities and infrastructure and, Responsibility, control, structure, and involvement of employees and teachers in the appropriate, harmonious and balanced division of tasks. Similarly, the Quality Management System is applied with respect to planning, implementation, and monitoring and evaluation. Taking into account various aspects: learning services for students; Educational facilities; School culture; Education financing; Attention and participation of the community or committee. Strictly speaking, the transformational leadership of the principal gives color to a conducive climate management and the quality of reliable learning, which ultimately determines the success of Madrasah quality.